The THE EFFECT OF PERCEPTED ORGANIZATIONAL SUPPORT, MOTIVATION AND JOB SATISFACTION ON EMPLOYEES' ORGANIZATIONAL COMMITMENT (CASE STUDY AT THE KENDAL REGENCY EDUCATION AND CULTURE OFFICE) - Kasmari Kasmari; Demi Eka Erawati; Teguh Pramono Hadi (International Journal Management and Economic, 2022)
ABSTRACT This study aims to identify the effect of perceived organizational support, motivation and job satisfaction on employee organizational commitment at the Kendal District Education and Culture Office. Employee organizational commitment is very important to avoid bad things such as the phenomenon of employees often leaving work during working hours, decreasing performance, increasing the number of employees who are not present, arriving late for work hours, and returning home earlier than normal working hours . This research is descriptive and causal research. The method used is a quantitative method with SPSS tools for processing data obtained by researchers. Data analysis used multiple linear regression analysis. The total population is 104 employees with sampling technique using saturated sampling or census. The results showed that: 1) Perceived Organizational Support had a positive and significant effect on Organizational Commitment because the beta value was 0.243 and the significance was 0.018 <0.05; 2) Motivation has a positive and significant effect on Organizational Commitment because the beta value is 0.490 and the significance is 0.000 <0.05 and; 3) Job Satisfaction has no effect on Organizational Commitment because the beta value is 0.067 and the significance is 0.586 > 0.05. Keywords: Perceived Organizational Support , Motivation, Job Satisfaction, and Organizational Commitment